Pliable natural biocide: Jaburetox is an intrinsically disordered insecticidal and fungicidal polypeptide derived from jack bean urease. (11th February 2015) - Lopes, Fernanda C.; Dobrovolska, Olena; Real‐Guerra, Rafael; Broll, Valquiria; Zambelli, Barbara; Musiani, Francesco; Uversky, Vladimir N.; Carlini, Célia R.; Ciurli, Stefano
Abstract : Jaburetox is a polypeptide derived from jack bean ( Canavalia ensiformis ) urease and toxic to a broad spectrum of insects, phytopathogenic filamentous fungi and yeasts of medical importance. The elucidation of the structural basis for the mode of action of Jaburetox is the focus of this multifaceted study. Jaburetox in solution is a monomer of 11.0 kDa featuring a large hydrodynamic radius, suggestive of a disordered polypeptide. The intrinsically disordered nature of Jaburetox was theoretically predicted by a comprehensive bioinformatics analysis and experimentally confirmed by light scattering as well as by circular dichroism and NMR spectroscopy. NMR signal assignment provided backbone secondary chemical shifts that indicated that Jaburetox has a low propensity to assume a stable secondary structure. 15 N relaxation studies revealed significant backbone mobility, especially in the N‐terminal portion of the polypeptide. The solution structure of Jaburetox shows the presence of an α‐helical motif close to the N terminus, together with two turn‐like structures situated in the central portion of the protein and close to the C terminus. Similar regions were predicted as potential protein–protein interaction sites using computational tools. The knowledge of the structural properties of Jaburetox in solution is a key step to correlate its structural and biological activities. Abstract : Jaburetox is a jack bean ( Canavalia ensiformis ) urease‐derived polypeptide. It is toxic to a broad spectrum of insects, phytopathogenic fungi and yeasts. We analyzed the structural basis for the Jaburetox action by multifaceted approach and showed that Jaburetox is an intrinsically disordered polypeptide with some residual structure. This knowledge is a key step to correlate its structural and biological activities.